Coffee-goat integrated system for assessing livelihood vulnerability (LVI-IPCC) and household food security in Lampung Province, Indonesia - KTUT MURNIATI; ZAINAL ABIDIN; FIRDASARI FIRDASARI; LINA MARLINA; AMANDA PUTRA SETA; MAULA ARIFATUZZAKIYAH; LAVITA WIRDA SARI (Smujo International, 2026)
Abstract. Murniati K, Abidin Z, Firdasari, Marlina L, Seta AP, Arifatuzzakiyah M, Sari LW. 2026. Coffee-goat integrated system for assessing livelihood vulnerability (LVI-IPCC) and household food security in Lampung Province, Indonesia. Asian J Agric 10 (1): g100151. https://doi.org/10.13057/asianjagric/g100151. This study analyzes the livelihood vulnerability and food security of farming households who implemented integrated coffee-goat farming system in Air Naningan Sub-district, Tanggamus District, Lampung Province, Indonesia. Primary data were collected through a structured survey of 88 farming households that selected purposively. Livelihood vulnerability was measured using the Livelihood Vulnerability Index-IPCC (LVI-IPCC) framework, which included three main components, namely exposure, sensitivity, and adaptive capacity. Household food security was classified based on a combination of the proportion of food expenditure and the level of energy consumption adequacy. The results showed an LVI-IPCC value was -0.00171, indicated as moderate vulnerability, with adaptive capacity relatively higher than the level of exposure. In terms of food security, 26% of households were classified food secure households, food vulnerable households (24%), food less secure households (39%), and food insecure households (11%). These findings confirmed that although coffee-goat integrated system strengthened the adaptive capacity of farming households, food security challenges remained a major issue that required more targeted policy interventions. The implications of these findings suggested that moderate vulnerability and unequal distribution of food security demand rural development policies that not only encourage agricultural integration but also strengthen household food diversification, income stabilization, and community-based nutrition interventions.